Early diagnostic and prognostic value of FEV₃/FEV₆ for COPD in underserved areas - Li, Fei; Han, Yancong; Yao, Xiaoling; Zhao, Fang; Zhao, Qing; Liu, Weilin (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) presents a major global health burden. While FEV1/FVC is the diagnostic gold standard, its application is limited by patient compliance and procedural complexity. FEV3/FEV6 has been proposed as a simpler alternative for early COPD screening, but its diagnostic and prognostic value remains unclear. This study aims to evaluate the effectiveness of FEV3/FEV6 in diagnosing mild to moderate COPD and predicting patient outcomes.MethodsA total of 200 patients suspected of having mild to moderate COPD underwent FEV3/FEV6 and FEV1/FVC testing from June 2019 to June 2021 and were followed for 3 years. Correlation analysis and ROC curve analysis were conducted.ResultsFEV6 correlated strongly with FVC (r = 0.981) and FEV3/FEV6 with FEV1/FVC (r = 0.928). FEV3/FEV6 showed high diagnostic accuracy (AUC = 0.953; sensitivity 87.92%; specificity 84.77%) and prognostic relevance (AUC = 0.783; sensitivity 80.3%; specificity 66.2%).ConclusionFEV3/FEV6 is a reliable tool for early diagnosis and prognosis assessment in mild to moderate COPD.